(untitled) (Periodicals of Engineering and Natural Sciences, 2021)
A low-cost, easy to fabricate real-time temperature sensation device built on an In-Line Mach–Zehnder interferometer basis was manufactured by fusing a segment of no-core fiber amongst two fibers of single-mode. Two different structures, tapered no-core fiber, and untapered no-core fiber both retaining acrylate polymer coating were investigated. The 3 cm length tapered no-core fiber sensor showed the highest sensitivities of ∼ −1.943 nm ◦C−1 and ∼ −1.954 nm ◦C−1 for two different dips respectively. The sensor exhibited high linearity with a very good resolution of 0.0102 ◦C. making the most of the high coefficient of thermal expansion, thermo-optic properties of the acrylate polymer, and the tapering effect, the sensor could be utilized in many temperatures observing applications like biochemical labs, biomechanical studies, and bio-sensing analyses.